Conflitos entre os estudantes do técnico em enfermagem - Goes, Nubia Cristina de (2019)
Those experienced in the training process of future health professionals, can influence professional life. Thus, this study aimed to understand the interpersonal conflicts in the perspective of the student of the technical course in nursing, know the students' perception of the conflicts, to identify the influence of the conflicts experienced in the classroom and to verify if the students feel the need for new behaviors to minimize conflicts. This is an exploratory study, descriptive, with a qualitative approach, conducted with 21 students of the nursing technical course of a private educational institution, of the interior of Rio Grande do Sul. There were used as instruments of data collection, the semi-structured interview and the focus group. The data were submitted to content analysis, seeking the construction of thematic categories by approximation or similarity. The recommendations set forth in Resolution 466/2012 of the National Health Council, with respect to the regulatory standards for research involving human beings, approved by the Research Ethics Committee of the UFSM, CAAE nº 67052817.6.0000.5346. From the analysis of the results, three thematic categories were originated: Conflict as a driving force for changes, which addressed the differences between conflict and confrontation, the motives that trigger conflict and teamwork; Experiences in the classroom and influences in preparation for professional life, which showed positive and negative influences for future nursing technicians; Communication and link building as strategies to minimize conflicts, emerging the need for dialogue and building links between students, the consolidation of assumed pacts and commitments, which can significantly contribute to the improvement of interpersonal relationships between the group. It is concluded that the participants of the research experience conflicts in the classroom, but they present difficulties in managing the situation. The need for behavioral change by the students to improve interpersonal relationships and to minimize existing conflicts was evidenced, counting on the collective construction of strategies that can help in this process.